Pengaruh Partisipasi Anggaran, Komitmen Organisasi, Gaya Kepemimpinan Terhadap Kinerja Manajerial - Putri, Zuwesty Eka (Esensi: Jurnal Bisnis dan Manajemen, 2014)
The purpose of this research was to analyze about the effect of budgetary participation, organizational commitment, and leadership styles on managerial performance.This is used primary data by the quetionnaries. Questionneries were distrubuted to principal, vice principal, along with his staff  involved in the preparation of the budget at a junior high school in South Tangerang as much as 54 quetionnaries. Number of quetionnaries returned was 43 quetionnaries. Sampling method used convinience sampling. The analysis method to examine hypothesis was regression analysis From the results of multiple regression, generate hypotheses such as the following,  that is: 1) Participation budget significant influence on managerial performance, 2) Organizational Commitment  significant influence on managerial performance, 3) Leadership style have no significant influence on managerial performance, 4) Budgetary participation, Organizational Commitment, and  leadership styles similarity significant influence on managerial performanceDOI: 10.15408/ess.v4i3.2439